Quilt local : finding inspiration in the everyday (with 40 projects) - Jones, Heather (STC Craft, 2015)
"For Heather Jones, inspiration can be anywhere. For her debut book, Quilt Local, she designed a collection of 20 quilts, each inspired by objects and places close to home--country roads, cityscapes, street signs--the landscape of her existence. Then, in a fascinating exercise in color theory and design play, she reworked each one in a second palette to show what a striking difference just a few basic changes can make. Pattern by pattern, Jones takes readers behind the scenes of her process, sharing photographs of her sources of inspiration, sketchbook pages, and the finished quilts. In addition, she offers an accessible lesson in color theory as it applies to quiltmaking." --